Experience in Laboratory Diagnostics of Falciparum Malaria and Dengue Co-infection with Eosinophilia: Case Report - Santoso, Aktaruddin Arief; Setyawati, Dita Mernita; Aulia, Fauqa Arinil; Burhanuddin, Mukhammad (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Indonesia is an archipelagic country with a tropical climate and is vulnerable to regional and global climate change impacts. Due to climatic factors, the country faces a high risk of vector-borne diseases such as malaria and dengue. Malaria and dengue are spread through vector mosquitoes. Concurrent malaria and dengue fever infections occur when these two diseases occur simultaneously in a person. There was a possible relationship between the immune response and hematological recovery after acute falciparum malaria. This case reported a patient with overlapping clinical features and the difficulties encountered in differential malaria-dengue diagnosis in a rural hospital in Jombang, East Java, Indonesia.